Electrodeposition of nanocrystalline FeXCo1-X thin films from choline chloride–urea deep eutectic solvents - Wu, Tingjun; Kim, Jiwon; Choa, Yong-Ho; Myung, Nosang V. (Frontiers in Chemistry, 2025)
FexCo1-x thin films were electrodeposited from a choline–urea deep eutectic solvent (DES) containing Fe3+ and Co2+ ions under ambient conditions. Anomalous co-deposition was observed, with Fe preferentially depositing over Co. With higher cathodic potential, the film’s morphology shifted from smooth to nodular. X-ray diffraction (XRD) analysis showed iron oxide impurities at lower overpotential and temperatures (e.g., <−0.9 V at 70 °C), while impurity-free, nanocrystalline Co50Fe50 films had formed at higher temperatures (e.g., 130 °C). The films exhibited a body-centered cubic (BCC) structure with (110) preferred orientation and grain sizes of 30 nm–40 nm.